2008
DOI: 10.1590/s1677-55382008000400012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence for a new therapeutic approach in renal cell carcinoma

Abstract: Purpose: Renal cell carcinoma (RCC) is the most lethal among the common urologic malignancies, comprising 3% of all human neoplasias; approximately 40% of patients eventually die of cancer progression. One third of patients who present with metastatic disease and up to 40% treated for localized disease generally experience recurrence. RCCs are characterized by high resistance to chemo-, radio-and immunotherapy. We recently discovered an endogenous enzymatic activity, which is particularly expressed in tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…RPV and EFV are toxic against pancreatic cancer cells at lowest concentrations. We found EC50s of EFV (31.5μmol/l and 49.0μmol/l) which are comparable to published concentrations that show anti-cancer cell activity in vitro (range 10–60μmol/l) [35, 7, 1113]. In BxPC-3 cells the lower toxic NNRTI concentrations induced apoptosis and the higher concentrations necrosis, whereas in the Panc-1 cells no increase of apoptosis was found.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…RPV and EFV are toxic against pancreatic cancer cells at lowest concentrations. We found EC50s of EFV (31.5μmol/l and 49.0μmol/l) which are comparable to published concentrations that show anti-cancer cell activity in vitro (range 10–60μmol/l) [35, 7, 1113]. In BxPC-3 cells the lower toxic NNRTI concentrations induced apoptosis and the higher concentrations necrosis, whereas in the Panc-1 cells no increase of apoptosis was found.…”
Section: Discussionsupporting
confidence: 81%
“…Published data report a toxic effect of EFV and NVP against cancer cells, whereas EFV is toxic at lower concentrations than NVP [4, 5, 7]. As a new generation of NNRTI has been developed, the question raised whether these drugs are also toxic against cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Nevirapine did not cause non-specific necrotic cell death or apoptosis in any of the tested cells, and the decrease in cell growth was correlated with accumulation of cells in the G1/G0 phase of the cell cycle, with a concomitant decrease in the S phase (Mangiacasale et al, 2003;Landriscina et al, 2005;Sciamanna et al, 2005). Although it has been suggested that an inhibition of endogenous non-telomeric RT by nevirapine is responsible for the interference with cell cycle progression Mangiacasale et al, 2003;Landriscina et al, 2005;Sciamanna et al, 2005;Landriscina et al, 2008;Pittoggi et al, 2008), the mechanisms underlying the anti-proliferative effects of nevirapine are poorly understood. Furthermore, while the effects of nevirapine on cell cycle progression have been studied in a number of cell types, the effect of nevirapine upon human hepatocytes, a target for nevirapine-induced toxicities has not been examined.…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have shown that exposure to nevirap-of cell growth in a variety of mouse and human cell lines (Mangiacasale et al, 2003;Landriscina et al, 2005;Sciamanna et al, 2005;Landriscina et al, 2008;Pittoggi et al, 2008). Nevirapine did not cause non-specific necrotic cell death or apoptosis in any of the tested cells, and the decrease in cell growth was correlated with accumulation of cells in the G1/G0 phase of the cell cycle, with a concomitant decrease in the S phase (Mangiacasale et al, 2003;Landriscina et al, 2005;Sciamanna et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…RCC tissue specimens were cultured by several different methods as previously described (Besch et al, 1983;Kim et al, 2008;Pittoggi et al, 2008) in DMEM medium (GIBCO, US) containing 1% penicillin, 1% streptomycin, 1% amphotericin B, 0.5% L-Glutamide and 20% fetal cattle serum. A portion of the primary culture and second generation cells were cryopreserved in liquid nitrogen.…”
Section: Primary Rcc Culturementioning
confidence: 99%